The effects of ketogenic metabolic therapy on mental health and metabolic outcomes in schizophrenia and bipolar disorder: a randomized controlled clinical trial protocol - Longhitano, Calogero; Finlay, Sabine; Peachey, Isabella; Swift, Jaymee-Leigh; Fayet-Moore, Flavia; Bartle, Toby; Vos, Gideon; Rudd, Donna; Shareef, Omer; Gordon, Shaileigh; Azghadi, Mostafa Rahimi; Campbell, Iain; et al. (Frontiers in Nutrition, 2024)
BACKGROUND: Schizophrenia, schizoaffective disorder, and bipolar disorder are debilitating conditions characterized by a chronic pattern of emotional, behavioral, and cognitive disturbances. Shared psychopathology includes altered affective states, disordered thoughts, and behavioral control. Additionally, those conditions share significant cardiovascular, metabolic, infectious, and respiratory co-morbidities, resulting in reduced life expectancy of up to 25 years. Nutritional ketosis has been successfully used to treat a range of neurological disorders and preclinical data have convincingly shown potential for its use in animal models of psychotic disorders. More recent data from open clinical trials have pointed towards symptom reduction in both schizophrenia and bipolar disorder. OBJECTIVES: to investigate the effects of nutritional ketosis via a modified ketogenic diet (MKD) over 14 weeks in stable community patients with bipolar disorder, schizoaffective disorder, or schizophrenia. DESIGN: A randomized placebo-controlled clinical trial of 100 non-hospitalized adult participants with a diagnosis of bipolar disorder, schizoaffective disorder, or schizophrenia who are capable of consenting and willing to change their diets. INTERVENTION: Dietitian-led and medically supervised ketogenic diet compared to a diet following the Australian Guide to Healthy Eating for 14 weeks. OUTCOMES: The primary outcomes include psychiatric and cognitive measures, reported in the Positive and Negative Symptoms Scale (PANSS), Young Mania Rating Scale (YMS), Beck Depression Inventory (BDI), WHO Disability Schedule, Affect Lability Scale and the Cambridge Cognitive Battery. The secondary metabolic outcomes include changes in body weight, blood pressure, liver and kidney function, lipid profiles, and markers of insulin resistance. Ketone and glucose levels will be used to study the correlation between primary and secondary outcomes. Optional hair cortisol and fecal microbiome composition analysis will be offered. Autonomic nervous system activity will be measured via wearable devices (OURA ring and EMBRACE wristband) in the form of skin conductance, oximetry, continuous pulse monitoring, respiratory rate, movement tracking, and sleep quality. Based on the results from preclinical research, clinical data from other neurodevelopment disorders, and open trials in bipolar disorder and schizophrenia, we predict that the ketogenic metabolic therapy will be well tolerated and result in improved psychiatric and metabolic outcomes as well as global measures of social and community functioning.